2020
DOI: 10.3390/ijms21051842
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonamide Inhibition Studies of an α-Carbonic Anhydrase from Schistosoma mansoni, a Platyhelminth Parasite Responsible for Schistosomiasis

Abstract: Schistosomiasis is a debilitating infection provoked by parasitic flatworms called schistosomes. The species Schistosoma mansoni is endemic in Africa, where it causes intestinal schistosomiasis. Recently, an α-carbonic anhydrase (CA, EC 4.2.1.1) was cloned and characterized from this organism and designated as SmCA. The protein is expressed in the tegument (skin) of S. mansoni at the host-parasite interface. Recombinant SmCA possesses high catalytic activity in the CO 2 hydration reaction, similar to that of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The third drug target, Carbonic anhydrase 2 (CA2), belongs to the plasma membrane anchored alpha carbonic anhydrases, which catalyse the reversible hydration of carbon dioxide and aid in intracellular pH regulation. Carbonic anhydrases are considered as potent anti-parasitic drug targets against protists, such as Trypanosoma , Leishmania (Vermelho et al ., 2017) and, recently, against blood flukes, schistosomes (Da'dara et al ., 2019; Angeli et al ., 2020). In the predicted three-dimensional model, the active site- and Zn binding residues of T. bryosalmonae CA2 retained similar positions as in SmCA, suggesting that similar therapeutic inhibitors may be used to target this protein in T. bryosalmonae .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The third drug target, Carbonic anhydrase 2 (CA2), belongs to the plasma membrane anchored alpha carbonic anhydrases, which catalyse the reversible hydration of carbon dioxide and aid in intracellular pH regulation. Carbonic anhydrases are considered as potent anti-parasitic drug targets against protists, such as Trypanosoma , Leishmania (Vermelho et al ., 2017) and, recently, against blood flukes, schistosomes (Da'dara et al ., 2019; Angeli et al ., 2020). In the predicted three-dimensional model, the active site- and Zn binding residues of T. bryosalmonae CA2 retained similar positions as in SmCA, suggesting that similar therapeutic inhibitors may be used to target this protein in T. bryosalmonae .…”
Section: Discussionmentioning
confidence: 99%
“…The schistosome alpha carbonic anhydrase plays a role in parasite virulence as its suppression using RNAi significantly reduced the establishment of parasite within host (Da'dara et al ., 2019). Several sulphonamide, thiol and hydroxamate substances have been shown to inhibit CA2 in Trypanosoma and Leishmania schistosomes (Vermelho et al ., 2017; Angeli et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…5 ). Furthermore, studies by several groups 4548 have reported the discovery of various aryl sulfonamide-based inhibitors for different isoforms of CA.…”
Section: Resultsmentioning
confidence: 99%
“…CAs are a superfamily of ubiquitous zinc metalloenzymes, present in all kingdoms of life, and encoded by at least eight distinct, evolutionarily unrelated gene families (designated α , β , γ , δ , ζ , η , θ and ι ) converging in the same crucial reaction, the reverse hydration of CO 2 to H + and HCO 3 − 15–18 . Recently our group reported the key molecular features of CA inhibitors (CAIs) binding to SmCA in comparison with human hCA II in order to understand the structural determinants directing affinity and selectivity 19 , 20 . Here, we report on the development of SmCA inhibitors conjugated to the PZQ scaffold as a possible novel therapeutic target for schistosomiasis.…”
Section: Introductionmentioning
confidence: 99%